Affective decision making: A theory of optimism bias - Anat Bracha; Donald J. Brown (Federal Reserve Bank of Boston, 2010)
Optimism bias is inconsistent with the independence of decision weights and payoffs found in models of choice under risk, such as expected utility theory and prospect theory. Hence, to explain the evidence suggesting that agents are optimistically biased, we propose an alternative model of risky choice, affective decision making, where decision weights - which we label affective or perceived risk - are endogenized. Affective decision making (ADM) is a strategic model of choice under risk where we posit two cognitive processes - the rational and the emotional process. The two processes interact in a simultaneous-move intrapersonal potential game, and observed choice is the result of a pure Nash equilibrium strategy in this game. We show that regular ADM potential games have an odd number of locally unique pure strategy Nash equilibria, and demonstrate this finding for ADM in insurance markets. We prove that ADM potential games are refutable by axiomatizing the ADM potential maximizers.
Keywords: D01; D81; G22; 330; Entscheidungstheorie; Entscheidung bei Risiko; Erwartungsnutzen; Theorie